Effect of particle sizes of magnesium oxide on zirconia toughened alumina vickers hardness - Ahmad Zahirani, Ahmad Azhar; Foo, Tai Kong; Hasmaliza, Mohamad; Mani Maran, Ratnam; Zainal Arifin, Ahmad (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.